Effect of selective catalytic reduction denitrification on fine particulate matter emission characteristics. (15th February 2019) - Cheng, Teng; Zheng, Chengqiang; Yang, LinJun; Wu, Hao; Fan, Hongmei
Highlights: SCR increases the emission of submicron particles and NH4 + and SO4 2− . Ammonium sulfates can improve the capture efficiency of ESP on submicron particles. The accumulated NH4 + in desulfurization slurry will generate new ammonium species and ammonia. Abstract: Selective catalytic reduction (SCR) may affect the emission characteristics of fine particulate matter due to NH3 slip during denitrification. In this study, an experimental facility equipped with a coal-fired boiler, SCR unit, electrostatic precipitator (ESP), and wet flue gas desulfurization (WFGD) unit was adopted to investigate the effect of SCR on final fine particulate matter emission characteristics. The migration and transformation of the generated ammonium sulfates and NH3 slip in the downstream ESP and WFGD were also investigated. The results indicate that SCR can increase the final emissions of submicron particles due to the formation of (NH4 )2 SO4 and NH4 HSO4 aerosols. In the ESP system, the generated ammonium sulfate particles can be effectively captured by the electric field force, which can also improve the capture efficiency of ESP on fine particles. Nonetheless, the operation of SCR with an NH3 injection still leads to an increase in fine particle emission levels at the ESP outlet. In the WFGD system, ammonium sulfates and ammonia can be partly removed by desulfurization through slurry scrubbing. However, the accumulated NH4 + in slurry will generate new ammonium species and ammonia through the entrainment and evaporation of the slurry. Finally, although both ESP and WFGD have a good removal effect on the generated fine particles, the SCR operation with the NH3 slip still results in an increase in the emission of fine particles and NH4 + . As the formation and transformation mechanism of ammonia slip and ammonium sulfates generated by SCR is complex and affected by many factors, further research will be required.